2009
DOI: 10.1016/j.physletb.2009.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Observation of γ-delayed 3α breakup of the 15.11 and 12.71 MeV states in 12C

Abstract: Deduced γ transitionThe reactions 10 B( 3 He, pααα) at 4.9 MeV and 11 B( 3 He, dααα) at 8.5 MeV have been used to investigate the γ decay of states in 12 C. By measuring the four-body final state in complete kinematics we are able to detect γ transitions indirectly. We find γ transitions from the 15.11 MeV state in 12 C to the 12.71, 11.83, 10.3 and 7.65 MeV states followed by their breakup into three α particles. The relative γ -ray branching ratios obtained are (1.2 ± 0.3), (0.32 ± 0.12), (1.4 ± 0.2) and (4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…To avoid four-body correlations all together, alternative ways of populating excited states in 12 C must be found, e.g., through the β decay of 12 B and 12 N [29] or γ decays from higher-lying states in 12 C [30].…”
Section: Extension To Broad Resonancesmentioning
confidence: 99%
“…To avoid four-body correlations all together, alternative ways of populating excited states in 12 C must be found, e.g., through the β decay of 12 B and 12 N [29] or γ decays from higher-lying states in 12 C [30].…”
Section: Extension To Broad Resonancesmentioning
confidence: 99%
“…[17,18] for details. We note that the detectors are insensitive to γ rays and neutrons; only charged particles are measured, but γ -ray and neutron energies can still be determined indirectly by use of energy and momentum conservation [19].…”
Section: Methodsmentioning
confidence: 99%
“…Recent inelastic α-scattering angular distribution studies also indicated the presence of a 2 + state at 9.84 ± 0.06 MeV of width 1.01 ± 0.15 MeV [5]. On the other hand, the study of 12 C * , produced in the β-decay of 12 N and 12 B, decaying into 3α continuum has however, not found clear evidence about the existence and nature of the 2 + states at excitations ∼10-12MeV [6] and also no evidence found in recent measurement of 3 He induced reactions on 10,11 B target [7]. In contrast, more recently, the γ induced 12 Be + α → α + α + α decay.…”
Section: Introductionmentioning
confidence: 99%
“…So, complete kinematical measurement of all outgoing particles in each event may be helpful in reconstructing the events originating from the decay of the excited states of the Hoyle state using missing energy (due to the emission of γ-ray) criterion. However, a recent experiment performed in this line [10], where complete kinematical measurement of all outgoing particles emitted from the reactions 10 2 2 + state. Since the spin and isospin zero α-particle is a very good projectile for the excitation of the nuclear IS states [9], we studied the decay of 12 C * into 3-body final states (3α) using inelastic α scattering from 12 C target to study the excited states of 12 C which are predominantly excitable through isoscalar transitions in general, and to look for a cleaner signature of the elusive 2 2 + state in particular.…”
Section: Introductionmentioning
confidence: 99%